The effect of platelet-rich plasma on ferroptosis of nucleus pulposus cells induced by Erastin - Shi-lin Lian; Jie Huang; Yan Zhang; Yu Ding (Biochemistry and Biophysics Reports, 2025)
Background: Intervertebral disc degeneration (IVDD) has been linked to ferroptosis, a type of programmed cell death. The role of platelet-rich plasma (PRP) in mitigating ferroptosis in nucleus pulposus (NP) cells within IVDD remains unclear. Purpose: This study aims to verify the effectiveness of PRP in reducing ferroptosis in NP cells induced by Erastin. Methods: Primary NP cells were isolated from SD rats, and a ferroptosis model was established using Erastin. PRP was prepared and applied to assess its impact on ferroptosis-related markers, including reactive oxygen species (ROS), iron content, and glutathione peroxidase 4 (GPX4). The effects of PRP on the ultrastructure of NP cells were also observed using transmission electron microscopy (TEM). Results: PRP treatment significantly restored GPX4 levels (431.47 ± 4.70 ng/L vs. 69.70 ± 4.06 ng/L, P < 0.05), reduced ROS levels (45.06 ± 3.78 vs. 155.36 ± 3.56, P < 0.05), and decreased iron content (32.24 ± 096 μg/L vs. 59.25 ± 3.72 μg/L, P < 0.05) in ferroptotic NP cells compared to the sham group. Additionally, PRP significantly increased the expression levels of collagen Ⅱ (0.72 ± 0.02 vs. 0.33 ± 0.02, P < 0.05) and aggrecan (0.81 ± 0.01 vs. 0.31 ± 0.02, P < 0.05) compared to the sham group. TEM analysis also showed improvements in mitochondrial ultrastructure. These findings suggest that PRP can alleviate ferroptosis and promote cellular recovery. Conclusions: The study demonstrates the potential of PRP as a therapeutic intervention in IVDD by mitigating ferroptosis in NP cells, offering a new theoretical basis for PRP treatment in degenerative disc diseases.